Catalytic growth of germanium oxide nanowires, nanotubes, and germanium nanowires : temperature-dependent effect - Yan, Chaoyi (2012)
One-dimensional GeO2 and Ge nanostructures, including nanotubes, nanowires, and branched nanowires, were synthesized using Au as catalysts. White products of GeO2 and brown products of Ge were fabricated at temperature regions of 500−600 and 300−400 °C, respectively. For the first time, we report the formation of single-crystalline GeO2 nanotubes and branched nanowires. Detailed growth mechanisms of the nanowires, nanotubes, and branched nanowires are presented. Fabrication of one-dimensional nanostructures with different configurations and compositions simultaneously from a single precursor enables the diversity of nanotube/nanowire synthesis, as well as their potential applications in nanoscale photonic and electronic devices.